Differential effects of sertraline in a predator exposure animal model of post-traumatic stress disorder - Wilson, C. Brad; McLaughlin, Leslie D.; Ebenezer, Philip J.; Nair, Anand R.; Dange, Rahul; Harre, Joseph G.; Shaak, Thomas L.; Diamond, David M.; Francis, Joseph (Frontiers in Behavioral Neuroscience, 2014)
Serotonin (5-HT), norepinephrine (NE), and other neurotransmitters are modulated in post-traumatic stress disorder (PTSD). In addition, pro-inflammatory cytokines (PIC) are elevated during the progression of the disorder. Currently, the only approved pharmacologic treatments for PTSD are the selective serotonin reuptake inhibitors (SSRI) sertraline and paroxetine, but their efficacy in treating PTSD is marginal at best. In combat-related PTSD, SSRIs are of limited effectiveness. Thus, this study sought to analyze the effects of the SSRI sertraline on inflammation and neurotransmitter modulation via a predator exposure/psychosocial stress animal model of PTSD. We hypothesized that sertraline would diminish inflammatory components and increase 5-HT but might also affect levels of other neurotransmitters, particularly NE. PTSD-like effects were induced in male Sprague-Dawley rats (n = 6/group x 4 groups). The rats were secured in Plexiglas cylinders and placed in a cage with a cat for 1 hour on days 1 and 11 of a 31-day stress regimen. PTSD rats were also subjected to psychosocial stress via daily cage cohort changes. At the conclusion of the stress regimen, treatment group animals were injected intraperitoneally (i.p.) with sertraline HClNorepinephrine at 10mg/kg for 7 consecutive days, while controls received i.p. vehicle. The animals were subsequently sacrificed on day 8. Sertraline attenuated inflammatory markers and normalized 5-HT levels in the central nervous system (CNS). In contrast, sertraline produced elevations in NE in the CNS and systemic circulation of SSRI treated PTSD and control groups. This increase in norepinephrine suggests SSRIs produce a heightened noradrenergic response, which might elevate anxiety in a clinical setting.